A patient with scleroderma associated with severe acro-osteolysis: A case report. Issue 2 (June 2022) - Zargaran, Mahsa; Rostamian, Atiyeh; Malek, Mahrooz; Rostamian, Abdolrahman
Systemic sclerosis is an autoimmune chronic sclerotic disease that can damage organs and cause serious complications for the patient such as musculoskeletal manifestations, Gastrointestinal involvement, pulmonary involvement, and renal disease. Acro-osteolysis is one of the musculoskeletal manifestations that causes corrosion of the bones in the fingertips of the hand and feet. In this paper, we have reported the rarely current evidence of severe Acro-osteolysis of the distal phalanges of the hands by radiological x-ray.